حوار نوح عليه السلام مع ابنه: دروس وعبر للداعيی: A Dialogue between Noh and His Son: Lessons for the Dawah Worker (Al Basirah, 2023)
This research paper presents a dialogue between Noh and his son, exploring the significance of effective communication and knowledge acquisition in the context of dawah (Islamic outreach). Through this dialogue, the importance of conveying the message of Islam with sincerity, humility, and compassion is highlighted. The exchange emphasizes the need for Muslims to be confident in their faith while acknowledging the limitations of their knowledge. It underscores the value of engaging in meaningful conversations, actively listening to others' perspectives, and building relationships based on mutual respect. The research emphasizes the role of personal example and the embodiment of Islamic principles in attracting others to the faith. Furthermore, the dialogue emphasizes the patience and persistence required in dawah, recognizing that guidance ultimately rests in the hands of Allah. This research serves as a reminder of the gradual nature of dawah and encourages Muslims to focus on conveying the message rather than fixating on immediate outcomes. It concludes that effective communication and continuous knowledge acquisition are essential components of successful Dawah efforts, facilitating the spread of Islam and fostering understanding among diverse individuals and communities.
Keywords: Dawah in through Quran; Dialogue; Diversity in the Society; Effective Communication in Dawah; Noh and His Son